2005
DOI: 10.1037/0021-9010.90.2.350
|View full text |Cite
|
Sign up to set email alerts
|

Negotiators' Bargaining Histories and Their Effects on Future Negotiation Performance.

Abstract: In 2 studies the authors show that the quality of deals negotiators reach are significantly influenced by their previous bargaining experiences. As predicted, negotiators who reached an impasse on a prior negotiation were more likely either to impasse in their next negotiation or to reach deals of low joint value compared to those who had reached an initial agreement. Notably, the impact of past performance on subsequent deals was just as strong for negotiators who changed partners on the 2nd occasion. Results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
58
0
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(61 citation statements)
references
References 34 publications
(52 reference statements)
2
58
0
1
Order By: Relevance
“…In the first case, more negotiation self-efficacy might lead to integrative negotiation and positive evaluations of negotiation outcomes. Some studies support that high selfefficacy improves effective negotiation behaviour (Gist et al, 1991;O'Connor et al, 2005;Stevens et al, 1993;Stevens & Gist, 1997;Sullivan et al, 2003), but studies on the relation between self-efficacy employment relations are rare and not unequivocal. Stevens et al (1993) found that respondents who had followed self-management training on negotiation tactics enhanced their negotiation skills.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the first case, more negotiation self-efficacy might lead to integrative negotiation and positive evaluations of negotiation outcomes. Some studies support that high selfefficacy improves effective negotiation behaviour (Gist et al, 1991;O'Connor et al, 2005;Stevens et al, 1993;Stevens & Gist, 1997;Sullivan et al, 2003), but studies on the relation between self-efficacy employment relations are rare and not unequivocal. Stevens et al (1993) found that respondents who had followed self-management training on negotiation tactics enhanced their negotiation skills.…”
Section: Discussionmentioning
confidence: 99%
“…According to Bandura perceived selfefficacy is 'concerned with people's beliefs in their capabilities to produce given attainments', or, 'to produce designated levels of performance that exercise influence over events that affect their lives' (Bandura, 1994;Bandura, 2001a). There is a wealth of research on self-efficacy related to a variety of domains (Bandura, 1997), but research on selfefficacy in relation to negotiation is relatively scarce (Gist, Stevens, & Bavetta, 1991;O'Connor & Arnold, 2001;O'Connor, Arnold, & Burris, 2005;Stajkovic & Luthans, 1998;Stevens & Gist, 1997;Sullivan, O'Connor, & Burris, 2003), and almost absent in combination with the employment relationship (Stevens, Bavetta, & Gist, 1993 and not among employees. For this reason, the opportunity occurred to design a new domain specific measuring instrument for negotiation self-efficacy (Bandura, 2001a).…”
mentioning
confidence: 99%
“…Consistent with this view, the very nature of the salesperson's role evolved conceptually over the years from that of Production, Sales, and Marketing orientations to that of Partnering, which focuses on building relationships that satisfy long-term customer and seller needs (Anderson and Huang, 2006;Wotruba, 1991). In the context of negotiations, O'Connor et al (2005) have also shown that bargaining histories are significant predictors of negotiation behavior and that, at least in some cases, researchers should conceptualize negotiations as interrelated exchanges rather than separable incidents. Therefore, examining business negotiations by extrapolating findings from one-time bargaining research is unlikely to capture the true nature of business negotiation processes and outcomes.…”
Section: Introductionmentioning
confidence: 97%
“…Uncertainty in revenues and costs can result in a negotiation impasse (Moon, Yao, and Park 2011). For a negotiator, failing to reach an agreement in previous negotiations is likely to lead to an impasse in the negotiator's subsequent negotiations (O'Connor, Arnold and Burris 2005). Misleading offers early in a negotiation by one party increases the likelihood of an impasse (Bac 2001).…”
Section: Gender Negotiation Outcomesmentioning
confidence: 99%